Update on Citrus Undercover Production Systems Research - Arnold Schumann; Laura Waldo; Alan Wright; Rhuanito Ferrarezi (EDIS, 2018)
In this article, we update research on CUPS (also known as citrus under protective screen) at the UF/IFAS Indian River Research and Education Center (IRREC) in Fort Pierce and the Citrus Research and Education Center (CREC) in Lake Alfred. The protected citrus experiments in both locations are about 1 acre each. Screen houses consist of 14-foot-high pole and cable frame architecture, covered with 50-mesh, anti-insect screen. In 2016–17, about 50 acres of commercial CUPS were established in Florida, with at least 150 more acres planned. There is now also strong interest for CUPS to be evaluated in California.